1990
DOI: 10.1212/wnl.40.4.714
|View full text |Cite
|
Sign up to set email alerts
|

Arachnoiditis ossificans with arachnoid cyst after cranial tuberculous meningitis

Abstract: A 34-year-old woman developed symptomatic arachnoiditis ossificans and an arachnoid cyst as a consequence of tuberculous meningitis adequately treated 20 years before. Surgical decompression of the cyst stopped the progression of her spastic paraparesis. Pathologic examination confirmed the presence of ossification of the arachnoid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
1
10
0
3
Order By: Relevance
“…However, arachnoiditis ossificans (AO) is a unique and uncommon phenomenon characterized by intrathecal bony metaplasia of the arachnoid membrane 1. This pathology develops following numerous predisposing processes including surgery, trauma, infection, myelography and subarachnoid hemorrhage 2,3,4. As of yet, the pathophysiology of AO is unknown; however, it may be a result of chronic inflammation of the arachnoid 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, arachnoiditis ossificans (AO) is a unique and uncommon phenomenon characterized by intrathecal bony metaplasia of the arachnoid membrane 1. This pathology develops following numerous predisposing processes including surgery, trauma, infection, myelography and subarachnoid hemorrhage 2,3,4. As of yet, the pathophysiology of AO is unknown; however, it may be a result of chronic inflammation of the arachnoid 5…”
Section: Introductionmentioning
confidence: 99%
“…Over 50 reports of AO are documented in literature; however, only eight of these are associated with syringomyelia 2,3,4,5,6,7,8,9. The pathophysiology of syrinx development in this disease state is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Van et al . 24 in 1990 reported one case of acquired spinal cord arachnoid cyst after tuberculous meningitis. Lolge et al 25 in 2004 also reported two such cases; the cyst in one was located at the anterior part of the foramen magnum.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory cells such as lymphocytes or neutrophils are usually absent, 15,18,27,29 except in one reported case of AO secondary to tuberculous meningitis 28 and in another case, that was found soon after the patient uderwent myelography. Inflammatory cells such as lymphocytes or neutrophils are usually absent, 15,18,27,29 except in one reported case of AO secondary to tuberculous meningitis 28 and in another case, that was found soon after the patient uderwent myelography.…”
Section: Histological Featuresmentioning
confidence: 97%
“…Magnetic resonance imaging is quite useful for diagnosis of associated features such as arachnoidal cyst, 1,21,28 intramedullary cavitation, 10,16,21 and meningocele. 1 Gadolinium enhancement of fibrous scars surrounding the nerve roots is indicative of the extension of arachnoiditis, 23 suggesting an occurrence prior to the ossification that acts as a matrix for the osseous process.…”
Section: Radiological Featuresmentioning
confidence: 99%